Connection of timber members. Issue 1 (July 2020) - Kuznetsov, Ivan; Gimranov, Linur
Abstract: Expanding applicability of timber structures, especially from engineered wood is a task of outmost importance due to wood's replenishment properties as a material. This paper review new modification of mentioned above connections in lattice timber structures. This connection is comprised of timber members with longitudinal slot in combination with lateral round holes and steel plate with laterally welded-in rods which is inserted into the slot from the side of the timber member in direction of the holes axis. The distance between holes is equal to the distance between welded-in rods. Welded-in rods essentially work as dowels providing mandatory installation of tightening bolts laterally to the plane in which steel plate is located. The bolt holes in the plate can be larger or equal to the bolt diameter. This research focused primarily on the development of calculation methods for the described connection validated by finite element models analysis and experimental data.